In vitro Antifungal Effects of Various Essential Oils against Aspergillus Crown Rot of Peanut - Merve Oğuz; Yusuf Gümüş; Soner Soylu (Turkish Journal of Agriculture: Food Science and Technology)
Synthetic fungicides that combat plant pathogenic fungi can enhance crop yields, ensuring stable crop production and market quality. However, the increase in the use of fungicides may cause to development of fungicide-resistant pathogen strains and the accumulation of fungicide residues in the food chain above safe limits. This situation underscores the need for improved fungal disease management through alternatives to synthetic fungicides. These alternatives include plant-derived compounds such as essential oils and extracts. Essential oils are known to be potent antifungal compounds against both human and plant pathogens. Aspergillus niger is a toxin-producing fungal disease agent that causes Aspergillus crown rot in peanuts. In this study, the antifungal activities of nine different essential oils from Foeniculum vulgare, Lippia citriodora, Origanum majorana, Origanum minutiflorum, Origanum onites, Origanum syriacum, Origanum vulgare, Salvia aramiensis and Thymus syriacus plants were evaluated against A. niger under in vitro conditions by using disc diffusion test. Among the nine essential oils tested, the highest antifungal activities were displayed by O. vulgare essential oil (with an inhibition zone diameter of 49.33 mm) which was followed by T. syriacus, O. onites, O. syriacum and O. minutiflorum essential oils (48.67, 47.00, 46.33 and 43.33 mm, respectively). The essential oils of F. vulgare, L. citriodora, and O. majorana showed relatively lower antifungal effects. The essential oil of S. aramiensis did not show antifungal effect against pathogen. The results indicated that plant essential oils could be valuable in promoting research aimed at developing new antifungal agent(s) for fungal disease management. However, further studies are needed to optimize the in vivo application conditions of essential oils against A. niger.